RNA sequencing data for responses to drought stress and/or clubroot infection in developing seeds of Brassica napus - Grégoire Bianchetti; Vanessa Clouet; Fabrice Legeai; Cécile Baron; Kévin Gazengel; Aurélien Carrillo; Maria J. Manzanares-Dauleux; Julia Buitink; Nathalie Nesi (Data in Brief, 2021)
Oilseed rape (Brassica napus L.) is the third largest oil crop worldwide. Like other crops, oilseed rape faces unfavorable environmental conditions resulting from multiple and combined actions of abiotic and biotic constraints that occur throughout the growing season. In particular drought severely reduces seed yield but also impacts seed quality in oilseed rape. In addition, clubroot disease, caused by the pathogen Plasmodiophora brassicae, limits the yield of the oilseed rape crops grown in infected areas. Clubroot induces swellings or galls on the roots that decrease the flow of water and nutrients within the plant. Furthermore, combinations of different stresses lead to complex plant responses that can not be predicted by the simple addition of individual stress responses. Indeed, an abiotic constraint can either reduce or stimulate the plant response to a pathogen or pest. Transcriptome datasets from different conditions are key resources to improve our knowledge of environmental stress-resistance mechanisms in plant organs. Here, we describe a RNA-seq dataset consisting of 72 samples of immature B. napus seeds from plants grown either under drought, infected with P. brassicae, or a combination of both stresses. A total of 67.6 Gb of transcriptome paired-end reads were filtered, mapped onto the B. napus reference genome Darmor-bzh and used for identification of differentially expressed genes and gene ontology enrichment. The raw reads are available under accession PRJNA738318 at NCBI Sequence Read Archive (SRA) repository. The dataset is a resource for the scientific community exploring seed plasticity.